ANALISA 10 UNSUR DAN PETA PERJALANAN PADA KARAKTER – KARAKTER DALAM FILM “LION” - William Sanjaya (Titik Imaji, 2022)
ANALYSIS OF 10 ELEMENTS AND TRAVEL MAP OF THE CHARACTERS IN THE FILM "LION". The film "Lion" is a drama film that tells about the struggle of a child from India who faces the phenomenon of transference, a phenomenon marked by past memories that appear and burden someone. Saroo's character is the main character in the story. Each character can be described with 10 elements through the life of the characters in a story. Characters also experience journeys that can be illustrated through 12 character journey maps. This study aims to explain the 10 elements and 12 stages of the character journey map in the “Lion” movie. This study uses a descriptive qualitative method by collecting sources and accurately analyzing the material for the "Lion" film. The theory used is the 10 elements theory of character proposed by Orson Scott Card and the 12 character journey theory by Christopher Vogler. Based on the research that has been done, it is concluded that each character has an element that can be seen from the character's actions throughout the story. Characters also go on journeys that can be elaborated through the 12 stages of the character journey map. Along the way, the characters also learn from every problem they face. The journey that the character faces will bring the character back to the original world by bringing the values that the character learns along the way.